Analysis of the association between Epstein Barr virus infection and Hodgkin lymphoma - Jasmine Akhter Jahan; S M Rashed Ul Islam; Md Shafikul Alam Tanim; Tasnim Binte Ahmed; Md Rabiul Alam; Ferdousy Begum (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Epstein Barr virus plays an important role in the pathogenesis of Hodgkin lymphoma. However, the frequency of its association in Bangladeshi people has not been widely studied. The aim of this study was to determine the association of Epstein Barr virus association in Hodgkin Lymphoma through detection of Latent Membrane Protein 1 by immunohistochemistry and serum Epstein Barr virus viral capsid antigen IgG antibody titer by serology. This was a cross-sectional study in purposively selected 45 histologically diagnosed cases of Hodgkin lymphoma at Bangabandhu Sheikh Mujib Medical University, Dhaka, during the period of March 2017 to December 2018. Latent membrane protein 1 was positive in 71.1% of cases of Hodgkin lymphoma. Among these positive cases, 96% of cases had significantly raised titer of serum Epstein Barr virus viral capsid antigen IgG antibody (P<0.0001 obtained by Fisher’s Exact test), which had a male predominance. Mixed cellularity classical Hodgkin lymphoma showed the highest positivity.